PROBLEMAS AMBIENTALES Y SUS EFECTOS EN EL DESARROLLO TURÍSTICO DEL CANTÓN EL EMPALME, PROVINCIA DEL GUAYAS, AÑO 2022. - Rosado Mosquera, Ana Maria (2022)
Environmental problems negatively affect the conservation of ecosystems, in turn represents a threat to the life of living beings and also directly affects the tourism development of the canton. The purpose of this research is to investigate the environmental problems and the effects they cause within the tourism development of the El Empalme canton, province of Guayas, year 2022. For the development of this study, the qualitative and quantitative method and field research were used. and documentary to obtain relevant information on the subject. In addition, a survey was carried out through Google Forms to 382 people from the Empalmese community to find out their opinions about the subject of study, obtaining as a result that the majority of the population has knowledge about environmental problems and recognize that the canton El Empalme is highly polluted, they jointly stated with 35.10% that the environmental problem that most influences the tourist development of the El Empalme canton is air pollution, also letting it be known that at present no awareness program has been developed within of the canton. Through this research, it is concluded that through an illustrative brochure, people can raise awareness and strengthen their participation in environmental protection actions, in order to obtain sustainable tourism development.